Quality and stability of the relationship as a function of distribution of housework, financial investments, and decision making between partners - Kamenov, Željka; Jelić, Margareta; Tadinac, Meri; Hromatko, Ivana (2007)
The social exchange theory postulates the satisfaction with the relationship to be lower for individuals whose costs and investments are higher than the rewards gained from the relationship. Rusbult’ s investment model of close relationships predicts that the greater the investment individuals make in the relationship, the less likely they are to leave, even if their satisfaction is low and other alternatives look promising. The aim of this study was to examine the role of the perceived distribution of housework, financial investments and decision making between partners in explaining both partners' perception of their relationship. The sample consisted of 418 married and cohabiting couples. Both partners independently evaluated the quality and stability of their relationship and their satisfaction with it. They also assessed the distribution of housework, financial investments and decision making in their relationship, as well as their satisfaction with that distribution. The highest satisfaction with the distribution of financial and decision making investments for both sexes was the one in which both partners contributed equally. As for the distribution of housework, while men are equally satisfied with any kind of distribution, women who perceive that they do most of the housework are the least satisfied. The satisfaction with the distribution of investments proved to be more important for the evaluation of the relationship than the actual distribution of investments. The satisfaction with the distribution of investments contributed to the relationship quality and satisfaction with it more than to the relationship stability. These results support both the social exchange theory and the equity theory.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG